Penerapan Academic Controversy Dalam Meningkatkan Aktivitas Belajar - Arif Hidayat (Al-Aulad: Journal of Islamic Primary Education, 2019)
The purpose of this study is to find out student learning activities before applying the Academic Controversy method, then the learning process using the Academic Controversy method, and student learning activities after applying the Academic Controversy method on social studies subjects in each cycle. The method used in this study is Classroom Action Research (CAR) which consists of four stages repeatedly, namely planning, action, observation and reflection. The technique of collecting data was carried out through the evaluation instruments of the pro and contra debates then with observation sheets for student and teacher activities. Based on the results of the study, the percentage of student learning activities before being applied to the academic controversy (academic controversy) method was only 31.2% with the less active category, after the application of the academic controversy (academic controversy) method in the first cycle student learning activities increased to 62 % included in the category is quite active. And student learning activities continue to increase in the second cycle which is at a very active stage which is 86%. From these data it can be concluded that the application of the method of academic controversy (academic controversy) can increase learning activities.